2002
DOI: 10.2165/00007256-200232150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Release During Acute and Chronic Aerobic and Resistance Exercise

Abstract: Exercise is a potent physiological stimulus for growth hormone (GH) secretion, and both aerobic and resistance exercise result in significant, acute increases in GH secretion. Contrary to previous suggestions that exercise-induced GH release requires that a "threshold" intensity be attained, recent research from our laboratory has shown that regardless of age or gender, there is a linear relationship between the magnitude of the acute increase in GH release and exercise intensity. The magnitude of GH release i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(118 citation statements)
references
References 123 publications
9
92
1
16
Order By: Relevance
“…Fryburg and Barrett (1993) reported that GH administration increases muscle protein synthesis and promotes muscle mass growth in humans. Also, it was reported that the acute response of GH correlates well with changes in muscle size and strength (McCall et al 1999;Wideman et al 2002). Moreover, GH response is stimulated by not only resistance exercise but also aerobic exercise depending on workload and duration.…”
Section: Growth Hormonementioning
confidence: 97%
See 1 more Smart Citation
“…Fryburg and Barrett (1993) reported that GH administration increases muscle protein synthesis and promotes muscle mass growth in humans. Also, it was reported that the acute response of GH correlates well with changes in muscle size and strength (McCall et al 1999;Wideman et al 2002). Moreover, GH response is stimulated by not only resistance exercise but also aerobic exercise depending on workload and duration.…”
Section: Growth Hormonementioning
confidence: 97%
“…It was also reported that the acute response of GH correlates well with changes in muscle size and strength (Wideman et al 2002;Velloso 2008). Therefore, GH responses after resistance exercise show adequate exercise stimulus (McCall et al 1999).…”
Section: Introductionmentioning
confidence: 93%
“…In the majority of studies, blood samples were used to determine the concentration level of GH and lactate before and after physical activities, yet few research studies present exercise results [26,27].…”
Section: Citationmentioning
confidence: 99%
“…Uma complexa inter-relação entre dois peptídios hipotalâmicos regula a liberação do GH na adenohipófise: a somatostatina (SRIF, growth hormone inhibit hormone), que inibe a secreção de GH, e o hormônio liberador de GH (GHRH, growth hormone releasing hormone) (Tirapegui, Fukushima, Grimaldi, 1993;De Palo et al, 2001). Tanto a síntese de GHRH como a de SRIF são influenciadas por diversos neurotransmissores, tais como a serotonina, a dopamina, a acetilcolina e a noradrenalina Wideman et al, 2002). Hormônios periféricos, como a insulina e os glicocorticóides, também influenciam a produção de GHRH e de SRIF, alterando, conseqüentemente, a síntese do GH (Silva, Lengyel, 2003).…”
Section: Aspectos Gerais Do Ghunclassified